Clinical background factors affecting outcomes of Helicobacter pylori eradication therapy in primary care. (10th April 2019) - Yokota, Nozomi; Ae, Ryusuke; Amenomori, Masaki; Kitagawa, Koji; Nakamura, Takuya; Yokota, Tetsuro; Masato, Kato; Sasahara, Teppei; Matsubara, Yuri; Kosami, Koki; Nakamura, Yoshikazu
Abstract: Objective: Few studies have reported the influence of clinical background factors on the outcome of Helicobacter pylori eradication therapy in primary care practice. We aimed to determine which clinical background factors influence the outcome of eradication therapy in a primary care setting. Methods: This was a retrospective study of patients who received H pylori eradication therapy at Higashiohmi City Gamo Medical Center, Shiga, Japan, from January 2012 to December 2015. We investigated clinical background factors associated with success, failure, and self‐interruption of H pylori eradication therapy: patients' age, gender, first‐ or second‐line treatment, reasons for receiving gastroenterological endoscopic examination, method of drug administration, and attending physicians' age and their specialties. Results: There were 369 patients (208 females, 161 male), with a mean age of 59 years (range 30‐88 years). The middle‐aged group (50‐69 years) was associated with successful eradication therapy compared with the young group (30‐49 years). The elderly group (>70 years) was associated with eradication therapy failure compared with the middle‐aged group. The young group was associated with self‐interruption of eradication therapy. There was a marginally significant association between male patients and self‐interruption. Older attending physicians (>50 years) were also associated with failure compared with younger physicians. There was no difference in outcome of eradication therapy between generalists and gastroenterology specialists. Conclusion: We have identified clinical factors associated with success, failure, and self‐interruption of H pylori eradication therapy in a primary care setting.